(untitled) (Docentes 2.0 Journal, 2015)
Research in Bolivian public universities is weak and has not been given enough relevance. Historically, university activity has focused on teaching and not on research, so that human resources trained and active in the exercise of research are scarce. The vast majority of university teachers are not involved in research activities or do so with a minimum workload as a secondary activity, after their teaching activity and administrative tasks.